Conceptualizing scaffold guided breast tissue regeneration in a preclinical large animal model - Cheng, Matthew; Janzekovic, Jan; Finze, Ronja; Mohseni, Mina; Saifzadeh, Siamak; Savi, Flavia M.; Ung, Owen; Wagels, Michael; Hutmacher, Dietmar W. (Bioengineering, 2024)
Scaffold-guided breast tissue regeneration (SGBTR) can transform both reconstructive and cosmetic breast surgery. Implant-based surgery is the most common method. However, there are inherent limitations, as it involves replacement of tissue rather than regeneration. Regenerating autologous soft tissue has the potential to provide a more like-for-like reconstruction with minimal morbidity. Our SGBTR approach regenerates soft tissue by implanting additively manufactured bioresorbable scaffolds filled with autologous fat graft. A pre-clinical large animal study was conducted by implanting 100 mL breast scaffolds (n = 55) made from medical-grade polycaprolactone into 11 minipigs for 12 months. Various treatment groups were investigated where immediate or delayed autologous fat graft, as well as platelet rich plasma, were added to the scaffolds. Computed tomography and magnetic resonance imaging were performed on explanted scaffolds to determine the volume and distribution of the regenerated tissue. Histological analysis was performed to confirm the tissue type. At 12 months, we were able to regenerate and sustain a mean soft tissue volume of 60.9 ± 4.5 mL (95% CI) across all treatment groups. There was no evidence of capsule formation. There were no immediate or long-term post-operative complications. In conclusion, we were able to regenerate clinically relevant soft tissue volumes utilizing SGBTR in a pre-clinical large animal model.